Common airborne Allergens and their clinical relevance in the Caracas valley - Perdomo Ponce, Doris; Salgado Labouriau, María; Hernández, Amador; ílvarezFernando; Rull, Valenli; Bolbochán, Diana; Guariglia, Mario; Suárez, Victor (Investigación Clínica, 2013)
In order lo detennine the sequential prevalence of pollen gratns and fungi spores in the city of Caracas by the volumetric melhod or collection and its effect on the populaton al. risk the first mutidisciplinary team of aerobiologtcal research was structured throegh a prolocol designed for fjve experimental stages namely: a) Determination of the climatological parameters: temperature relative humidity, speed and wind direciotion, precipitation and atmospheric stabllity, through simultaneous records of’ meteorological status located in the metropolitan area of Caracas: b) Collection, identification. Classification and determination of the local distribution of the most important pollen grains existing in the zone under study: c) Collection, identification and classification of the most important fungi spores in the area; d) Preparation of the first pollinic calendar of Caracas and e) Evaluation of possible implication of the environment and the response through the IgE antibody in the selected patients in the area under study. Our results show: 1) The climatic conditions existing during the sampling period coincide with the analysis of the last 20 years in the Valley of ’Caracas. 2) The Venezuelan Central University (UCV) station was elected as the most representative point for pemanent sampling. 3) An ideal statistical method is obtained in order lo determine the spatial arrangement in the sampler rod of’ a dense type of’ fungi spores typical of the area under study. 4) The fistpollinic calendar of Caracas was structured and 5) A seasonal tendency of the IgE response is shown. These results suggest an evident interrelation between the suggested concept of poliseasonality and antigenic polysensitization. and between individual seasonality with a specific reactivity ando, finally, between tropical mixed seasonality with the expressíon of combíned respíratory pathologíes ín our environment.